INFLUENCE OF COCONUT SHELL ADDITION ON PHYSICO-MECHANICAL PROPERTIES OF WOOD PLASTIC COMPOSITES1 - Hillig,Éverton (2017)
ABSTRACT In this study, composites with three types of thermoplastic matrix and cellulosic material in a proportion of 40% were produced. The three thermoplastic matrices were high density polyethylene (HDPE), polypropylene (PP) and low density polyethylene (LDPE), and the cellulosic materials were pure wood flour (Pinus taeda L) or a mixture of wood flour and coconut shell flour (Cocus nucifera L) in equal ratios. The objective was to evaluate the influence of addition of coconut shell on the physico-mechanical properties (density, strength and rigidity) and the distribution of the cellulosic material in the thermoplastic matrix of the manufactured composites. It was found that the composites had a satisfactory distribution of wood flour in thermoplastic matrices, but the addition of coconut shell promoted bubble formation in the resulting pieces and, thus, interfered with the material properties. The use of a coupling agent promoted interfacial adhesion (cellulose - thermoplastic matrix), which was better in high density polyethylene composites, followed by polypropylene and low density polyethylene. In general, the coconut shell addition caused a decrease of all properties compared to composites made with Loblolly Pine. In addition, the interactions between thermoplastic type and cellulosic matrix type have been statistically confirmed, which caused variations in the studied properties